Pengaruh Lingkungan Budaya terhadap Implementasi Bisnis Skala Internasional - Firda Fitriani; Munawaroh Munawaroh (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the influence of cultural environment on the implementation of international-scale business. In the current era of globalization, companies operating in international markets must be able to adjust their business strategies to various cultural factors present in the target countries. A different cultural environment can influence various aspects of business operations, including communication, negotiations, decision-making, and human resource management. This study uses a qualitative approach with case studies to understand how multinational companies adapt their strategies when facing cultural challenges in different countries. The findings show that the success of international business implementation highly depends on a deep understanding of local cultural values, as well as the ability to adapt products, services, and communication strategies according to the norms and customs in place. This study also identifies the challenges and opportunities faced by companies in managing cultural diversity to achieve success in international business.